Temporal price analysis of sorghum (Sorghum bicolor) in selected markets, Sudan - Elhori, Abubakr I S (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2018)
This study conducts temporal price analysis of sorghum crop prices of Khartoum, Madani, Gadaref, Dongola and Alfashir markets in order to identify seasonal price patterns and their expected changes over time as compared to their storage costs. The analytical approach upon which this study was based is so called "classical model". The study based preliminary on secondary data collected from Agricultural Statistics Department, Ministry of Agriculture and Forests during period 2007-2015. The study found that the seasonal prices spread increased about 16% from the index low to the high on average for Khartoum market, about 19% for Madani, 17% for Gadaref, 21% for Alfashir and 11% for Dongola, while the annual interest rate of the year 2015 was 10%.  Thus monthly price variations indicate an opportunity to capture above normal returns to storage. Causes of these prices differences are inadequate transportation, marketing infrastructure and government policy.